PENGARUH PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT BERBANTUAN MEDIA DIGITAL BAAMBOOZLE TERHADAP MINAT BELAJAR SISWA DALAM PEMBELAJARAN PENDIDIKAN PANCASILA MATERI HAK DAN KEWAJIBAN DI KELAS IV SD - Aulya Izzati Hakim, Alvina; Mahya Fanny, Arif (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning interest is an important factor that influences the success of learning. In Pancasila Education learning, especially the material of rights and obligations, students' learning interest is still relatively low as indicated by the lack of attention, participation, and enthusiasm during the learning process. Therefore, this study aims to determine the effect of implementing the Teams Games Tournament (TGT) cooperative learning model assisted by Baamboozle digital media on the learning interest of fourth-grade elementary school students. This study uses a quantitative approach with a pre-experimental design in the form of One Shot Case Study. The research subjects were one class of fourth-grade students as the experimental class, while the object of the research was students' learning interest. Data collection was carried out using a learning interest questionnaire and observation sheets after the implementation of the learning model. Data were analyzed using descriptive statistics, normality tests, and One Sample t-Test hypothesis tests with the help of IBM SPSS Statistics 31. The results showed that the average value of students' learning interest was 60.96 which is included in the high category. The normality test showed that the data was normally distributed, namely Sig. 0.113 which is greater than 0.05, while the One Sample t-Test hypothesis test produces a significance value of 0.003 which is smaller than 0.05, so the null hypothesis is rejected and the alternative hypothesis is accepted. This finding proves that the implementation of the Teams Games Tournament (TGT) type cooperative learning model assisted by Baamboozle digital media has an effect on students' learning interest in Pancasila Education learning on the material of rights and obligations. The results of this study are expected to be a reference for teachers in designing more interactive Pancasila Education learning based on digital games. Keywords: Cooperative Learning, Teams Games Tournament, Baamboozle, Learning Interest, Pancasila Education